Effect of functionalization of colloidal gold on controlled flocculation by the ligand-receptor mechanism - Kogut, A.M.; Voronov, A.S.; Kislenko, V.N.; Peukert, Wolfgang (Russian Journal of Applied Chemistry, 2005)
Modification of colloidal gold particles with octadecanthiol and alkyl biotin, with the subsequent flocculation of these particles via introduction of a tetramer protein avidin, was studied.
Keywords: Gold; Biotin; Flocculation; Gold Particle; Colloidal Gold